(untitled) (Emancipação, 2023)
Veterinary Medicine experiences an increase in the number of female professionals. They tend to be incorporated into areas related to companion animals, to the detriment of other areas of activity. Thus, the study aimed to analyze the perspectives of professional insertion of female students of Veterinary Medicine at Unifesspa, campus of Xinguara/PA, trying to perceive gender inequalities. Data were collected through questionnaires answered by professors and students, of both sexes, from the Unifesspa Veterinary Medicine course. Qualitative data were analyzed using content analysis and quantitative data submitted to descriptive statistics. Although a large part of the student body does not agree with the sexist assumptions that permeate Veterinary Medicine, a sexual division of labor persists, reinforced by some professors and agricultural producers in the region. The sexual division of labor dissuades the insertion of undergraduates in work related to production animals, considered male attributions.